Microbiological activity of probiotic drugs in interaction with antibiotics - Матвєєва, О. Л.; Омельчук, С. О.; Решетняк, Л. Р. (Problems of Environmental Biotechnology, 2018)
Proven expediency of use probiotic drugs to normalize the state of beneficial microbiota of intestine and the possibility of analyzing the activity of lactic acid microorganisms in the interaction with antibiotics of various species has been proved to determine the effectiveness of the probiotic action of drugs with antibiotic therapy.